Clinical Decision Support and Closed‐Loop Control for Intensive Care Unit Sedation. Issue 2 (19th March 2013) - Haddad, Wassim M.; Bailey, James M.; Gholami, Behnood; Tannenbaum, Allen R.
Abstract Critical care patients undergoing surgery require drug administration to regulate physiological variables such as blood pressure, cardiac output, heart rate, and degree of consciousness. The rate of infusion of each administered drug is critical, requiring constant monitoring and frequent adjustments. Patients in the intensive care unit who require mechanical ventilation due to acute respiratory failure also frequently require the administration of sedative agents. Open‐loop control (manual control) by clinical personnel can be tedious, imprecise, time‐consuming, and sometimes of poor quality, depending on the skills and judgment of the clinician. Dynamical system pharmacokinetic and pharmacodynamic modeling and closed‐loop control system design methodologies can significantly advance our understanding of the wide effects of pharmacological agents and anesthetics, as well as advance the state‐of‐the‐art in active control of drug delivery systems for clinical pharmacology. In this paper, we discuss the challenges and opportunities of clinical decision support and closed‐loop control for intensive care unit sedation.